Climate-smart agriculture: a synthesis of empirical evidence of food security and mitigation benefits from improved cropland management - Branca G; McCarthy N; Lipper, Leslie; Jolejole MC (Food and Agriculture Organization of the United Nations, 2011)
Meeting the food demand of a global population expected to reach 9.1 billion in 2050 and over 10 billion by the end of the century will require major changes in agricultural production systems. Improving cropland management is key to increasing crop productivity without further degrading soil and water resources. At the same time, sustainable agriculture has the potential to deliver cobenefits in the form of reduced GHG emissions and increased carbon sequestration, therefore contributing to climate change mitigation. This paper synthesizes the results of a literature review reporting the evidence base of different sustainable land management practices aimed at increasing and stabilizing crop productivity in developing countries. It is shown that soil and climate characteristics are key to interpreting the impact on crop yields and mitigation of different agricultural practices and that technology options most promising for enhancing food security at smallholder level are also effective for increasing system resilience in dry areas and mitigating climate change in humid areas.